Mechanistic insights into the mode of action of anticandidal sesamol. (September 2016) - Ansari, Moiz A.; Fatima, Zeeshan; Hameed, Saif
Abstract: Previously we have deciphered the antifungal effect of sesamol (Ses), a phenolic compound obtained from sesame oil, against human fungal pathogen Candida albicans . To gain deeper insights into the possible mechanisms involved, transcription profiling was done in presence of Ses which revealed various targets through which Ses was barricading the growth of C . albicans . We observed that Ses perturbs membrane integrity confirming our previous observations and displayed disrupted plasma membrane ATPase activity. We further investigated that Ses leads to inhibited morphological transition, biofilm formation and epithelial cell adhesion which are significant virulence attributes required for pathogenesis. Interestingly, Ses also causes amendment in iron homeostasis as revealed by hypersensitivity under iron deprivation, ferroxidase assay to estimate iron levels and concomitant upregulation of FTR2, a high affinity iron transporter. Finally we assessed that Ses causes defect in mitochondrial functioning and DNA repair mechanism. Together, being source of consumable natural product, further studies on Ses are warranted so that it can be exploited as effective antifungal agent. Graphical abstract: Highlights: Ses disrupts membrane homeostasis in Candida albicans independent of calcineurin signaling. Ses inhibits dimorphic switching in C . albicans . Ses inhibit biofilm formation and cell adhesion in C . albicans . Ses disrupts iron homeostasis and mitochondrial functioning in C . albicans . Ses affects DNA repair mechanism but not cell cycle regulation in C . albicans .